2020
DOI: 10.1111/aphw.12206
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Affective Trajectory in a Positive Psychology Intervention

Abstract: Enhancing positive affect (PA) and reducing negative affect (NA) are targets of positive psychology interventions, and well-being and positive functioning are core elements of mental health. However, the underlying temporal dynamics of these elements are unknown. This study aimed at identifying how a 42-day daily positive psychology intervention (PPI) impacts affective longitudinal dynamics compared to a control condition. This study employed an experience sampling method (selfobservation diary including the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…The current research also contributes to our understanding on the role of affective experiences on meant health and well-being (as measured by GHQ and the flourishing measure) by demonstrating the mediating effects of positive and negative affect on the severity of mental health distress and experience of flourishing. The results that positive and negative affect completely mediated the relationship between risk perception and mental health distress confirmed experience of negative affect as a risk factor of mental health and verified the buffering effect of positive affect in coping with mental health distress in face of stressful life events (Congard et al, 2020;Fredrickson et al, 2003;Ong et al, 2006;Steptoe et al, 2009;Tugade & Fredrickson, 2007). This complete mediation effect also highlighted the central role of emotional experiences during the pandemic in influencing people's mental health and the adaptive functions of positive affect in dealing with the mental health impacts of this emergent public health crisis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The current research also contributes to our understanding on the role of affective experiences on meant health and well-being (as measured by GHQ and the flourishing measure) by demonstrating the mediating effects of positive and negative affect on the severity of mental health distress and experience of flourishing. The results that positive and negative affect completely mediated the relationship between risk perception and mental health distress confirmed experience of negative affect as a risk factor of mental health and verified the buffering effect of positive affect in coping with mental health distress in face of stressful life events (Congard et al, 2020;Fredrickson et al, 2003;Ong et al, 2006;Steptoe et al, 2009;Tugade & Fredrickson, 2007). This complete mediation effect also highlighted the central role of emotional experiences during the pandemic in influencing people's mental health and the adaptive functions of positive affect in dealing with the mental health impacts of this emergent public health crisis.…”
Section: Discussionsupporting
confidence: 57%
“…This complete mediation effect also highlighted the central role of emotional experiences during the pandemic in influencing people's mental health and the adaptive functions of positive affect in dealing with the mental health impacts of this emergent public health crisis. Given that prioritizing positivity by enhancing the experience of positive emotions can safeguard people from mental health distress (Catalino et al, 2014;Congard et al, 2020), the current research results have implications for developing brief, effective, and scalable interventions to decrease negative affect and increase positive affect during this public health crisis. Researchers already initiated trials on enhancing positive affect and reducing negative affect through brief online interventions by changing reappraisal styles for adaptive emotion regulation during the COVID-19 pandemic (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Negative emotions are considered a significant risk factor in affecting mental health, whereas there is possibly a buffering effect of positive affect in coping with mental stress. [ 21 ] Overall positive and negative emotional responses in study participants were equivalent with no significant difference between them. It was also observed that stress factors and stress levels had a strong correlation with negative emotions, thus highlighting the significance of lowering the stress levels in HCWs with appropriate coping mechanisms to maintain positive mental health.…”
Section: Discussionmentioning
confidence: 89%
“…ESM and smartwatch sensing are suitable for (a) assessing well-being and distress as psychological, momentary states (as opposed to enduring traits ) within an individual over time and within contexts (Conner et al, 2009) and (b) may help to personalize interventions by determining what works best for whom under which conditions and why (Renner et al, 2020). Although there are studies using ESM to show variations of psychological states in daily life, there are only a handful of studies that demonstrate the effectiveness of PPIs using ESM (Congard et al, 2020; McKee et al, 2020; Teixeira & Freire, 2020). Importantly, PPI effectiveness studies employing ESM target an entirely new way of delivering PPIs in contrast to classical PPI programs that have an average length of 6 weeks or 10 sessions (see the recent meta-analysis by Carr et al, 2021).…”
Section: The Present Studymentioning
confidence: 99%